An Approach to Heparin and Lidocaine Hypersensitivity for the Interventional Nephrologist. Issue 5 (8th January 2014) - Sequeira, Adrian
Abstract The general and interventional nephrologist may occasionally encounter a situation where the patient may state that he/she has an allergy to lidocaine or heparin. Heparin hypersensitivity is usually either a delayed type hypersensitivity reaction or an immune‐mediated thrombocytopenia. While a number of alternative drugs are available, many of them are subject to local availability, food and drug administration indications, and the patient's hepatic and renal function. Many of these drugs do not have antidotes in case of bleeding. Lidocaine hypersensitivity is usually a delayed type reaction, although adverse reactions, which are much more common, are wrongly labeled as an allergy. 1% diphenhydramine and benzyl alcohol may be used as alternatives.